2008
DOI: 10.3846/1822-427x.2008.3.145-151
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of deflections of bridge girders strengthened by carbon fibre reinforcement

Abstract: The paper deals with experimental and theoretical investigations in reinforced concrete structures strengthened with carbon fibre sheets. Four stages in the behaviour of concrete structures strengthened with the carbon fibre reinforced polymer (CFRP) are distinguished. A method for calculating the deflections of such structures is presented. The design procedure for defining the strength of the structures evaluates the stiffness of the contact between the carbon fibre and the concrete. Experimental investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
(15 reference statements)
0
11
0
1
Order By: Relevance
“…Experimental researches (Marčiukaitis et al 2007;Skuturna et al 2008;Daugevičius et al 2012;Skuturna, Valivonis 2014, 2015 show that flexural stiffness increases due to the increased depth of the neutral axis. However, thin CFRP plates do not change the crosssection of the strengthened element.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental researches (Marčiukaitis et al 2007;Skuturna et al 2008;Daugevičius et al 2012;Skuturna, Valivonis 2014, 2015 show that flexural stiffness increases due to the increased depth of the neutral axis. However, thin CFRP plates do not change the crosssection of the strengthened element.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most advantageous material types for strengthening is fibre-reinforced polymers (FRP) due to their corrosion resistance and high strength to low weight ratio [1][2][3][4][5]. Anticorrosion properties are particularly relevant in aggressive environments, for example, bridge structures [6]. Strength properties could be used even more efficiently and economically by prestressing the FRP material [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the applications where accessibility conditions allow wrapping a member with FRP composites, such as FRP wrapping of RC columns, has no problem regarding a debonding issue (Buyukozturk et al 2004). Considering the use of FRPs for external strengthening of the external reinforcement of other types of concrete elements, Xiong et al (2007), Kim et al (2008a, b), Skuturna et al (2008), Diab et al (2009), and Daugevičius et al (2012) found that additional anchoring was essential in order to assure FRP-to-concrete bond strength.…”
Section: Frp Materials Properties and Types Of Manufacturingmentioning
confidence: 99%